Compétences communicationnelles et pratiques numériques des « musiciens connectés » - Stéphane COSTANTINI (Tic & Société)
Since the 2000s, the emergence of new players from the communication industries has provoked profound upheavals within the music industries. This paper examines the challenges faced by musicians in developing communication skills on the Internet and digital social networks. Their deployment of rationale for action similar to those used in community management highlights new challenges for the dissemination and promotion of musical activities. An empirical analysis of musicians’ discourse and practices in France and the United Kingdom suggests that the communication practices of the musicians encourage them to adopt an entrepreneurial stance regarding their visibility. This stance is controversial in more than one respect.